Cannabinoid Receptor 2 Modulates Neutrophil Recruitment in a Murine Model of Endotoxemia - Theodore S. Kapellos; Carlota Recio; David R. Greaves; Asif J. Iqbal (Mediators of Inflammation)
The endocannabinoid system consists of endogenous lipid mediators and cannabinoid receptors (CB) 1 and 2. It has previously been demonstrated that activation of the leukocyte-expressed CB2 has anti-inflammatory effects in vivo. Here, we report its role under baseline conditions and in a model of low-dose endotoxemia by comparing CB2 knockout to littermate control mice. CB2-deficient mice displayed significantly more neutrophils and fewer monocytes in the bone marrow under steady state. In initial validation experiments, administration of 1 mg/kg LPS to male C57BL/6J mice was shown to transiently upregulate systemic proinflammatory mediators (peaked at 2 hours) and mobilise bone marrow neutrophils and monocytes into circulation. In CB2 knockout mice, the level of the metalloproteinase MMP-9 was significantly elevated by 2 hours and we also observed augmented recruitment of neutrophils to the spleen in addition to increased levels of Ccl2, Ccl3, Cxcl10, and Il6. Collectively, our data show that the absence of CB2 receptor increases the levels of innate immune cell populations in the bone marrow under steady state. Furthermore, during an acute systemic inflammatory insult, we observe a highly reproducible and site-specific increase in neutrophil recruitment and proinflammatory chemokine expression in the spleen of CB2 knockout mice.